The relationship between educational priorities and students' religious attitudes - Awwalina Khairunnisa (Trigin Institute, 2022)
The family's function, particularly how parents care for their children at home, has a significant impact on how youngsters develop their religious spirit. The attention of parents and the roles of each parent should complement one another in order to create a whole and harmonious family that can best carry out religious orders. If parents don't pay attention to their kids and miseducate them, kids will be readily swayed by things that are bad. Based on Islamic religious principles given in the Koran and the Prophet's sunnah, Islamic religious education shapes a person's physical and spiritual qualities. It is anticipated that both facets will develop in harmony in order to prevent a disconnect between spiritual and material requirements. Selfishness will be avoided if a person leads a balanced life. The goal of this study is to ascertain the extent to which parental involvement in the delivery of Islamic religious education and its relevance to students' religious attitudes are related. This study employs the descriptive analytic method and uses interviews and questionnaires as its data sources. Data analysis, a crucial step in the scientific method, is done to use the study that has been done on the sampled pupils to provide a response to the research question. By analyzing the data, it can be concluded that parents give their children's religious education a lot of thought, which has an impact on the religious attitudes of students who behave well. In addition, the school fulfills its responsibility as an educational institution by offering lessons and extracurricular activities that can help students develop their religious attitudes, as can be seen from interviews with the school.